MiR-361-3p regulates FSH by targeting FSHB in a porcine anterior pituitary cell model. Issue 3 (March 2017) - Ye, Rui-Song; Li, Meng; Li, Chao-Yun; Qi, Qi-En; Chen, Ting; Cheng, Xiao; Wang, Song-Bo; Shu, Gang; Wang, Li-Na; Zhu, Xiao-Tong; Jiang, Qing-Yan; Xi, Qian-Yun; et al.
Abstract : FSH plays an essential role in processes involved in human reproduction, including spermatogenesis and the ovarian cycle. While the transcriptional regulatory mechanisms underlying its synthesis and secretion have been extensively studied, little is known about its posttranscriptional regulation. A bioinformatics analysis from our group indicated that a microRNA (miRNA; miR-361-3p) could regulate FSH secretion by potentially targeting the FSHB subunit. Herein, we sought to confirm these findings by investigating the miR-361-3p-mediated regulation of FSH production in primary pig anterior pituitary cells. Gonadotropin-releasing hormone (GnRH) treatment resulted in an increase in FSHB synthesis at both the mRNA, protein/hormone level, along with a significant decrease in miR-361-3p and its precursor (pre-miR-361) levels in time- and dose-dependent manner. Using the Dual-Luciferase Assay, we confirmed that miR-361-3p directly targets FSHB. Additionally, overexpression of miR-361-3p using mimics significantly decreased the FSHB production at both the mRNA and protein levels, with a reduction in both protein synthesis and secretion. Conversely, both synthesis and secretion were significantly increased following miR-361-3p blockade. To confirm that miR-361-3p targets FSHB, we designed FSH-targeted siRNAs, and co-transfected anterior pituitary cells with both the siRNA and miR-361-3p inhibitors. Our results indicated that the siRNA blocked the miR-361-3p inhibitor-mediated upregulation of FSH, while no significant effect on non-target expression. Taken together, our results demonstrate that miR-361-3p negatively regulates FSH synthesis and secretion by targeting FSHB, which provides more functional evidence that a miRNA is involved in the direct regulation of FSH.